Circulating LPS and (1→3)-β-D-Glucan: A Folie à Deux Contributing to HIV-Associated Immune Activation - Ramendra, Rayoun; Isnard, Stéphane; Mehraj, Vikram; Chen, Jun; Zhang, Yonglong; Finkelman, Malcolm; Routy, Jean-Pierre (Frontiers in Immunology, 2019)
Immune activation is the driving force behind the occurrence of AIDS and non-AIDS events, and is only partially reduced by antiretroviral therapy (ART). Soon after HIV infection, intestinal CD4+ T cells are depleted leading to epithelial gut damage and subsequent translocation of microbes and/or their products into systemic circulation. Bacteria and fungi are the two most abundant populations of the gut microbiome. Circulating lipopolysaccharide (LPS) and (1→3)-β-D-Glucan (βDG), major components of bacterial and fungal cell walls respectively, are measured as markers of microbial translocation in the context of compromised gut barriers. While LPS is a well-known inducer of innate immune activation, βDG is emerging as a significant source of monocyte and NK cell activation that contributes to immune dysfunction. Herein, we critically evaluated recent literature to untangle the respective roles of LPS and βDG in HIV-associated immune dysfunction. Furthermore, we appraised the relevance of LPS and βDG as biomarkers of disease progression and immune activation on ART. Understanding the consequences of elevated LPS and βDG on immune activation will provide insight into novel therapeutic strategies against the occurrence of AIDS and non-AIDS events.